“Achilles Heel” of a Practical Psychologist in the Field of Russian Education - Pakhalyan, V.E. (Bulletin of Practical Psychology of Education, 2023)
The author's vision of the problems of professionalism of a practical psychologist of education and understanding of both the origins of the appearance of weak points in professional training and possible ways to overcome them are presented. It is noted that the level of compliance of qualifications with the requirements for the work of a practical psychologist of education can be set by the lack of development of the legal and methodological foundations of activity, the quality of special education; the degree of development / severity of certain professionally important qualities in a specialist. Ways to overcome this state of affairs are identified: a) improvement of the regulatory framework and requirements for activities; b) definition and consolidation in the professional lexicon of methodological foundations specific to practical psychology; c) harmonization of the content of the Federal State Educational Standard and the standards of professional activity; d) scientific and practical substantiation and consolidation of the place and role of professionally important qualities, both in the selection for training, in the qualification at graduation from the university, and in the certification procedure for the qualification. Представлено авторское видение проблем профессионализма практического психолога образования и понимание как истоков появления слабых мест профессиональной подготовки, так и возможных путей их преодоления. Отмечается, что уровень соответствия квалификации практического психолога образования требованиям к работе может быть связан с непроработанностью правовых и методологических оснований деятельности, качеством специального образования; степенью развития / выраженности тех или иных профессионально важных качеств у специалиста. Выделены пути преодоления такого положения дел: а) совершенствование нормативно-правовой базы и требований к деятельности; б) определение и закрепление в профессиональном лексиконе специфических для практической психологии методологических оснований; в) приведение в соответствие содержания ФГОС и стандартов профессиональной деятельности (ПС); г) научно-практическое обоснование и закрепление места и роли профессионально важных качеств как при отборе на обучение, при присвоении квалификации при выпуске из вуза, так и в процедуре аттестации при присвоении квалификации.